2012
DOI: 10.1186/1756-0500-5-593
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal solitary fibrous tumor of the pelvis with pollakiuria: a case report

Abstract: BackgroundSolitary fibrous tumor (SFT) is rare soft tissue tumor, and it occurs most commonly in the pleura. Retroperitoneal SFT is generally found by palpable mass or abdominal distention. Here we report a case of SFT presenting pollakiuria.Case presentationA 64-year-old man was referred to our hospital for pollakiuria. Contrasted-enhanced computed tomography revealed a heterogeneously enhanced pelvic tumor of approximately 10 × 8 × 7 cm. Invasion of the surrounding organs, distal metastasis, and lymph node s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…1,2 Although mostly occurring in the pleura, this tumour has also been recently reported in many sites, including abdomen, trunk, extremities and the head and neck region. [3][4][5][6][7][8] In our study, eight SFT in the head and neck region were located in the orbit, masticator space, the parapharyngeal space and the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Although mostly occurring in the pleura, this tumour has also been recently reported in many sites, including abdomen, trunk, extremities and the head and neck region. [3][4][5][6][7][8] In our study, eight SFT in the head and neck region were located in the orbit, masticator space, the parapharyngeal space and the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Although rare, SFT could also be found in various head and neck regions, such as the cheek, orbit, oral cavity, laryngeal and parapharyngeal spaces as well as the thyroid gland, [4][5][6][7] and the common sites affected in the head and neck region are the orbit and oral cavity. 7,8 Classically, SFT are composed of variably pleomorphic spindle cells admixed with collagen and arranged haphazardly.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological characteristics of malignant SFT include hypercellular lesions, cytological atypia, numerous mitoses (four or more mitoses per 10 high-power fields), tumor necrosis, and/or infiltrating margins [8]. Vallat-Decouvelaere et al reported malignancy in eight of 92 cases of extrathoracic SFT, including local recurrence or distal metastasis, in seven of which at least one of the typical pathological characteristics was observed in the primary tumor [9]. Various benign or malignant soft tissue tumors emerging from fat, muscle, and nerve may develop in the retroperitoneal region.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary fibrous tumors (SFTs) are rare, non-functional, and generally benign mesenchymal tumors, with an estimated age-standardized incidence of 1.4 per million population ( 1 , 2 ). Despite the fact that SFTs are mainly intrathoracic ( 1 ), on rare occasions they can appear in extrapleural sites, such as the retroperitoneal ( 3 ) and pelvic regions ( 4 ). In total, 10–20% of SFTs are classified as malignant, and eventually lead to mortality ( 1 ).…”
Section: Introductionmentioning
confidence: 99%